Static Analysis of Single Shaft Hub Wheel Cover to Determine The Strength Level of The Cover - Kurnia, Ishak Rizaldy Eka; Muttaqin, Benazir Imam Arif; Huki Chandra (LPPM Telkom University Surabaya, 2024)
The cover on the wheel hub serves to protect the most important components and support the weight coming from the body, so it must be designed as well as possible to support the existing weight. The cover on the wheel hub also functions as a balance when driving so that the cover is made with strong material and is not easy to corrode because the part is often subjected to mechanical pressures. The problems that occur in the Nusantara Energy Manufacturing company (MEN) make researchers want to develop a cover design on a single shaft wheel hub to increase the strength of the cover in receiving pressure from vehicles, drivers, and passengers. In this research, a simulation study is carried out to design the cover and perform static simulations to determine the value of deformation and stress that occurs in the single shaft wheel hub cover. The material used in the cover design is Aluminum Alloy 6061 with a load value of 2177 N and 2912 N. The maximum deformation value on the MEN cover is 0.272 mm, a strain value of 0.007, and a stress value of 730.805 N/m2 with a load of 2177 N. At 2912 N loading, the maximum deformation value is 0.111 mm, a strain value of 0.003, and a stress of 307.538 N/m2. It can be concluded that the MEN cover has a higher static value than the YMMotorcover. There are several factors such as the thickness of the cover on the parts used as supportpoints.